Study of environmental, social, and paternal factors in preterm delivery using sibs and half sibs. A population-based study in Denmark. Issue 1 (1st January 1999) - Basso, O; Olsen, J; Christensen, K
Abstract : OBJECTIVE: The aim of this study was to evaluate the influence on preterm delivery of changes in putative genetic and environmental risk factors between two consecutive births. Low social status is a suspected risk indicator of preterm delivery, but the impact of social mobility has not been studied before. PARTICIPANTS: The study uses national cohorts in which women act as their own controls. Subjects were identified by means of registries: 10, 455 women who gave birth to a preterm child and had a subsequent live birth between 1980 and 1992 and 9849 women who gave birth to a child after 37 completed weeks of gestation and had a subsequent live born child in the same time period formed the cohorts. METHODS: The risk of having a premature infant in the subsequent pregnancy was analysed in each cohort as a function of changes in male partner, residency, occupation, and social status between the two pregnancies. RESULTS: There was a strong tendency to repeat a preterm delivery (18% v 6% in the general population). Social decline was associated with a moderate increase in the recurrence risk (OR: 1.22; 95% CI: 1.02, 1.47). In the reference cohort the risk of preterm delivery associated with changing from a rural to an urban municipality was 2.03 (95% CI: 1.14, 3.64). CONCLUSIONS: Social decline and moving to an urban municipality may be associated with preterm delivery.